Rancang Bangun Boiler Panci Presto untuk Setrika Uap dengan Penambahan Komponen Indikator Level Air - Muhamad Zainudin; Ziyadatul Husna (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research was motivated by several laundries that use pressure cooker steam iron boilers for the ironing process. However, there are still users who find it difficult to estimate water level. If the water in the pressure cooker dries up or runs out whitout knowing it, then this can be dangerous and have a bad impact both on the user and in terms of the quality of the pot. So the aim of this research is to modify the pressure cooker steam iron boiler by adding a water level indicator whose function is to determine the water capacity during the ironing process, so that it is hoped that it can minimize work accidents. The method use is descriptive quantitative. From the design process, the tool was then tested to determine the starting time for using the iron using pressure variations of 15 psi, 20 psi, and 22 psi. From the research results, it was found that the design process was carried out through several stages, including the measurement process, drilling process, and assembly process. The test results started that the optimal pressure was 20 psi, because at this pressure the steam produced was optimal with a heating time of a 58 minutes.